Production performance and meat quality of local ducks fed rations containing extract of torch ginger (Etlingera elatior) flowers and betel (Piper Betle linn) leaves - Ristika Handarini; Elis Dihansih; Dewi Wahyuni; Burhanudin Malik (Faculty of Animal Science, Universitas Brawijaya, 2021)
Compared to chickens, ducks still have low productivity and other limitations. One of the causes of these problems might be attributed to the off-odor found in duck meat. Therefore, production performance and meat quality of ducks need to be improved. The inclusion of extracts of betel (Piper betle Linn) leaves and torch ginger (Etlingera elatior) flowers wereas done to improve production performance and meat quality of local ducks. This study was aimed at assessing the effects of the inclusion of betel leaves and torch ginger flowers in the basal rations on production performance and meat quality of local ducks in the growing phase. A completely randomized factorial design in 4 x 4 with three replicates was used. The first factor consisted of four levels of torch ginger flower solution, namely 0, 2.5, 5, and 7.5%. The second factor consisted of four levels of betel leaf solution, namely 0, 2.5, 5, and 7.5%. Results showed that no significant differences (P>0.05) were found in body weight gain, feed intake, feed conversion, mortality rate and meat quality (pH, water holding capacity, tenderness and cooking loss). It was concluded that the inclusion of extract of betel leaves and torch ginger flowers did not improve production performance and meat quality of male local ducks.